Late onset pancytopenia post chimeric antigen receptor T cell therapy triggered by a COVID-19 vaccination: a case report - Maciocia, Nicola; Spencer, Dean; Maciocia, Paul; Childerhouse, Anna; O’Reilly, Maeve; Payne, Elspeth; Roddie, Claire (Frontiers in Hematology, 2024)
Cytopenia is a common side effect after chimeric antigen receptor T cell (CAR-T) therapy but is unusual at late timepoints when it is most commonly due to bone marrow (BM) failure, myelodysplasia (MDS) or other secondary malignancies. In this case report, we describe a patient who developed severe aplastic anaemia 18 months after CD19 CAR-T therapy, and shortly after COVID-19 vaccination. This is the first description of severe aplastic anaemia triggered by COVID-19 vaccination as a cause of post-CAR-T cytopenia. The patient described was treated with a combination of eltrombopag and ciclosporin due to frailty and had a rapid and complete clinical response to this therapy, providing an effective option for the treatment of immune-related cytopenia post-CAR-T in an increasingly elderly and frail population.